Peran Career Development Center (CDC) Upaya Pengembangan Mahasiswa di Universitas Wiralodra Indramayu - Nurpratama, Meddy; Yudianto, Agus; Firdaus, Taufansyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
A number of universities have established Career Development Centers (CDC) or career development units, designed to assist students in understanding career-related materials and making informed career decisions. In reality, not everyone has equal opportunities to secure a good and promising job. Therefore, it is not surprising that many people flock to find employment. Wiralodra University faces challenges due to the absence of CDC (Career Development Center) services, making it difficult for students to obtain the advice and materials needed to advance their professions. The Career Development Center (CDC) plays a crucial role in student development, primarily focusing on enhancing career readiness. CDC not only provides efficient, up-to-date job vacancy information but also aims to support the career development of students and alumni through counseling services, alumni experience sharing, and training to prepare them for the challenges of the job market. Evaluations conducted by CDC, based on criteria tailored to specific needs, have shown that this program has made a significant impact. Students involved with the CDC experience increased career readiness, quick access to relevant information, and build strong relationships with industries, all contributing to the comprehensive development of students in achieving their career goals